ANALYZING THE EFFECT OF DENSITY VALUE DEVIATION ON PRINT QUALITY - Romi Setiawan; Soebardianto .; Septia Ardiani (Politeknik Negeri Media Kreatif, 2020)
The quality control activities, in particular the measurement of density values, are part of the quality control parameters carried out by each company. Companies sometimes forget about the quality parameters of the name, even though the quality can give the printed products a good guarantee in the eyes of consumers. To achieve the quality level, of course, the business does not stand idle, there are several things that need to be done or provided by the business to support the quality, namely man (human), machine (machine), material (material), and method (method). In the development of technology in an increasingly advanced digital world, companies want to continue to compete with a digital world by making inroads, this of course gives the products produced by the company a good or a good level of quality. In this discussion, there is an identification of problematic aspects arising from the deviation of density values as well as ways to obtain standard density values and factors that affect the quality of prints on book cover prints using a Heidelberg machine.Keywords—Quality Control, Density, Standart, Product, Deviation